Quality Assurance And The Philippine Education System: Inputs From Future Filipino School Leaders - Ancho, Inero (LPM IHDN Denpasar, 2019)
This study involves future education leaders and managers in the Philippines and their conceptual understanding of â€œqualityâ€ in the context of education, the streams of teaching and learning to be specific. Respondents were enrolled in a graduate program in a teacher education institution based in Manila, Philippines and were asked the following: (1) concepts identified with quality; (2) conceptual understanding of quality assurance; (3) quality assurance mechanisms employed in the Philippine education system; and (4) proposed quality assurance mechanisms to uplift the academic achievement of Filipino students. Â It has been revealed that while future education leaders and managers possess sufficient ideas and knowledge about quality assurance, it is still vital to provide them with technical know-how and discourses on the theoretical-practical connection of quality and studentsâ€™ academic achievement. Quality assurance mechanisms being implemented are considered to be effective in the Philippine education system.Â